Evacuation Plan for Potential Victims of Jyotinagar Landslide at Butwal (The Nepali Mathematical Sciences Report, 2024)
Butwal, a city in Rupandehi district of Nepal, is a rapidly expanding business hub. The city's geographical location, population density, and lack of proper planning make it extremely vulnerable to natural calamities. Emergency evacuation is a major issue during disasters in such cities. The landslide, known locally as the Jyotinagar Landslide, poses a deadly risk in Butwal and requires an effective evacuation plan. The literature contains a variety of evacuation strategies for evacuation scenarios around the world that are based on the available resources and the types of disasters. In this study, we propose a mathematical optimization evacuation plan, as no such plan exists so far, for possible victims of the Jyotinagar Landslide at Butwal, Nepal, using the Lexicographical Maximum Dynamic Contraflow Algorithm.